Parental suicide attempt and offspring educational attainment during adolescence in the Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort. Issue 10 (11th April 2016) - Geulayov, G.; Metcalfe, C.; Gunnell, D.
Abstract : Background: Few studies have investigated the impact of parental suicide attempt (SA) on offspring outcomes other than mental health. We investigated the association of parental SA with offspring educational attainment in the Avon Longitudinal Study of Parents and Children (ALSPAC). Method: Parental SA was prospectively recorded from pregnancy until the study children were 11 years old. National school test results (ages 11–16 years) were obtained by record linkage. Multilevel regression models quantified the association between parental SA and offspring outcomes. Results: Data were available for 6667 mother–child and 3054 father–child pairs. Adolescents whose mothers had attempted suicide were less likely than their peers to achieve the expected educational level by age 14 years [adjusted odds ratio (aOR) 0.63, 95% confidence interval (CI) 0.41–0.95] in models controlling for relevant confounders, including parental education and depression. At age 16 years, adolescents whose mothers had attempted suicide were less likely to obtain the expected educational level (five or more qualifications at grade A*–C) (aOR 0.66, 95% CI 0.43–1.00) in models controlling for relevant confounders and parental education; however, after additionally controlling for maternal depression the results were consistent with chance (aOR 0.74, 95% CI 0.48–1.13). Findings in relation to paternal SA were consistent with those of maternal SA but power was limited due to lower response rate amongst fathers. Conclusions: Maternal SA was associated with diminished educational performance at age 14 years. Educational attainment during adolescence can have substantial effect on future opportunities and well-being and these offspring may benefit from interventions.